Bridge the college‐to‐career gap with focused initiatives. Issue 7 (24th February 2018) - Sutton, Halley
Abstract : SAN DIEGO — Career services should help to serve as the bridge between your students' academic present and their professional future, but do your career services actually help your students? According to a survey conducted by the California Community Colleges System, only 17 percent of CCCS students who used the career services available at their campus found them helpful. With the CCCS looking to create 1 million skilled workers for the state, the initiative to create the Strong Workforce Program, which targets outcomes in areas of student success, along with other measures of quality in curriculum, regional collaboration, and career pathways, was born.